Hubungan Budaya Organisasi dan Kompetensi dengan Kinerja Guru - Nelma Liklikwatil (Jurnal Bimbingan dan Konseling Terapan, 2017)
Teachers will have a good performance if the teacher in carrying out his profession as well as possible in accordance with the principles of professional teachers and supported by the compensation and culture of a good school organization as well. This study aims to determine the relationship between organizational culture and compensation with teacher performance. Methods Survey research with correlational approach. The population in this study is the teacher of State Senior High School 2 Ambon as many as 93 people. The sample was determined using random sampling technique. The number of sample research as many as 50 people and test samples of 40 people. Hypothesis testing shows that 1) there is a positive and significant relationship between organizational culture and performance. It is shown by the value of correlation coefficient (r) equal to (0,641) and tcount 2,645 bigger than ttable (2,011), 2) there is positive and significant correlation between compensation with teacher performance. The correlation coefficient (r) obtained is 0.527 and the tcount (4.923) is greater than the ttable (2.011); 3) there is a significant relationship between organizational culture and compensation with teacher performance, the value of the multiple correlation coefficient (R) 6,070) and the value of Fhitung (19,151) is greater than Ftable (5,641). There is a coherent relationship between organizational culture and compensation with teacher performance.